Analisis Pelayan Tunarungu terhadap Pembeli (Studi Kasus pada Difabis Coffee & Tea) - Margareta, Vita; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In life, humans need each other, and to communicating with each other. With communication, humans can exchange messages and thoughts with listeners. Both verbally and non-verbally so that feedback occurs. In the current era of globalization, many Indonesians are creating businesses that are in line with trends among millennials, opening interesting and unique coffee shops. This research was conducted in a coffee shop